Return migration issues in Kazakh-Chinese relations: Mobility and immobility in migration of Kazakh diaspora in China - Dalelkhan, Aibolat; Mazhidenova, Dariko; Azmukhanova, Aiman; Tuleshova, Lyazzat; Aliyeva, Saule (Opción)
In the paper the Kazakhstan migration research is carried out, its role in social and economic life of Republic is defined, main stages are established. Recommendations on improving Migration policy of the Republic of Kazakhstan are proposed. As a result of the research, it was revealed that the current Law on Migration of the Republic of Kazakhstan may not positively stimulate the process of resettlement of ethnic Kazakhs from China. It is recommended to work directly with Kazakh youth abroad in order to give a new impetus to the process of migration of the Kazakh diaspora to Kazakhstan